Anatomical alterations: biparietal thinning in antiquity. Review of published cases and a new case - Rossetti, Nicol; Fusco, Roberta; Vanni, Arianna; Garanzini, Francesca; Mazzucchi, Alessandra; Licata, Marta (Anthropological Review, 2025)
Cranial anatomical variations, such as biparietal thinning, offer critical insights into the health and living conditions of ancient populations. Despite the presence of extensive archaeological records, biparietal thinning remains a relatively rare and understudied condition. This review aims to synthesize existing bioarchaeological literature on biparietal thinning, addressing its historical prevalence, geographical distribution, and potential etiologies. This study integrates data from previous bioarchaeological research supplemented with a new case from skeletal remains excavated at the hypogeal cemetery of Santa Maria Maggiore in Vercelli, Northern Italy. The analysis included macroscopic examination, radiological imaging, and comparative analysis with clinical and paleopathological cases to identify and assess the characteristic features of biparietal thinning. Our analysis of the skeletal remains of an old adult female individual revealed clear indicators of biparietal thinning. Notably, the thinning was bilateral, with the absence of diploe in the affected areas while maintaining the inner and outer tables of the cranial vault. These findings align with documented cases in the literature and contribute new data to the limited corpus of biparietal thinning cases. This study underscores the importance of integrating paleopathological findings with modern medical knowledge to enhance the understanding of ancient diseases. The case from Vercelli provides an opportunity to explore the multifactorial origins of biparietal thinning and highlights the necessity of a multidisciplinary approach, combining archaeological, anthropological, and medical perspectives. By presenting this new case, we aim to stimulate further research into biparietal thinning and similar cranial pathologies, enriching the broader narrative of human health evolution.